KAJIAN PENGARUH PENAMBAHAN NANO SiO2 PADA NILAI KOHESI DAN SUDUT GESER DALAM TANAH LEMPUNG EKSPANSIF KARAWANG - Oktaviani, Ike; Sampurna, Henry; Putra, Jon; Ngirtjuk, Ngirtjuk (Jurnal Sains dan Teknologi ISTP, 2024)
Expansive clay soil is soil that has a high potential for shrinkage expansion and has a good bearing capacity under water-unsaturated conditions but poor under water-saturated conditions. So expansive clay soil has poor soil properties and is less profitable when used as the basis of a building construction. The results of data analysis tests it can be concluded that the cohesion value of expansive clay soil after adding a mixture of variations of Nano Silica Dioxide (SiO₂), namely original soil + Nano SiO₂ 2% = 33.03 kPa (increased 8.5%), original soil + Nano SiO₂ 3% = 46.26 kPa (up 21.73%), Natural soil + Nano SiO₂ 4% = 51.43 kPa (up 26.9%) Percentage of Nano Silica Dioxide (SiO₂) mixture is directly proportional to the soil cohesion value. The greater the percentage of Nano Silica Dioxide (SiO₂) mixture, the greater the cohesion value. The highest soil cohesion value is found in the 4% Nano Silica Dioxide (SiO₂) mixture. Changes in shear angle values ​​in expansive clay soil after adding a mixture of various polyamide fibers, namely original soil + Nano SiO₂ 2% = 26.57◦, original soil + Nano SiO₂ 3% = 29.36◦, original soil + Nano SiO₂ 4% = 32 .01◦. concluded that the percentage of Nano Silica Dioxide (SiO₂) mixture is directly proportional to the value of the friction angle in the soil. The greater the percentage of Nano Silica Dioxide (SiO₂) mixture, the greater the value of the internal friction angle. The highest internal shear angle value is found in the 4% Nano Silica Dioxide (SiO₂) mixture.